Calculation Analysis of Fatigue Strength for Heavy Locomotive Axle - WU Zhong-liu; LEI Cheng; XIAO Shou-ne; YANG Guang-wu (机车电传动)
A certain 30 t locomotive axle was verified based on the latest standards TB/T 2395-2008 of design method for powered axle, and the concrete computation steps were proposed. By contrast of finite element method, the axle fatigue strength was proved to meet the design requirements, stress difference reasons of which were analyzed. With different setting value, magnitude of interference was found have great influence on stress of wheel-axle-fitting place.